(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
This paper is an analysis and reflection on one of the first experiences of institutionalization of the memory and human rights policies of Argentina: the Provincial Commission for the Memory of the Province of Buenos Aires. In this paper, the creation of the organization is historicized and the main tensions that it was going through in relation to its state nature, the autonomy of the governments, the scope of the objectives defined by the law and the implementation of the programs. In particular, the analysis focuses on the relationship that has been built between memory policies of state terrorism and the defense and denunciation of violations of human rights in democracy, a core that explains the different tensions that experience.